Action research – connecting practice and theory. Issue 2 (15th March 2018) - Ulvik, Marit; Riese, Hanne; Roness, Dag
Abstract: Teacher education is often criticised for not being relevant and for there being a lack of continuity between practice teaching and the university coursework. In the literature, action research is presented as a way to bridge the gap and connect the two. The present article explores, through a qualitative study, how research-based knowledge communicated at the university and experiences from practice teaching interact in student teachers' action research projects. The study also explores the outcome, for the student teachers, of conducting research in their practicum. The findings show that student teachers use theory and research in many different ways, and they are both consumers and producers of research. They especially emphasise the outcome of theory interacting with real situations encountered in the teaching practice. Contributing to a positive impact on their outcome were the opportunity they are offered to reflect on their own practice, the possibility they have to focus on something they find important, and the chance to make their own experiences with a particular tool for professional development.